(untitled) (Al-Academy, 2025)
The aesthetics of a sustainable theatrical environment have displaced the stereotypical constants in the recipient’s intellectual structure and shaped a change in the contemporary recipient’s awareness. The theatrical environment was the proposed space for shaping the director’s vision of the show’s creator and stimulating the recipient’s participation. The study sheds light on four chapters (the first - methodological, which includes the research question: Does the theatrical environment have sustainable aesthetics? The research aims to: identify the aesthetics of a sustainable theatrical environment in contemporary Iraqi performances. The research was set in 1999, spatially, to the Department of Art Education, and thematically, to study the aesthetics of a sustainable theatrical environment in contemporary Iraqi performances The second chapter (the theoretical framework) includes two topics, the first: the aesthetics of the theatrical environment, and the second: sustainable Iraqi performances. The researcher reviewed some previous studies and presented indicators of the theoretical framework. The third chapter (research procedures, the research community, and the descriptive analytical research method on the intentional sample model according to the research tools and indicators). The fourth chapter (the research results and their discussion), the most prominent of which are: the multiplicity of spatial foci in the open environment, which supported the visual formation, which contributed to producing an environment with aesthetic value, to achieve the aesthetic effect. The conclusions: the theatrical environment constituted a qualitative addition to the visions of the Iraqi director, and constituted one of the variables witnessed by the path of contemporary theatrical art The researcher made some recommendations, including: adopting a theatrical festival specializing in environmental performances in locations that have a special kind of aesthetics, similar to the countries of the world. The researcher suggested future studies, including: the theatrical environment between text and performance in Iraqi theater (Iraqi models). The research concluded with a list of sources, references, images, and a summary of the research.